ANALYSIS OF TRIGLYCERIDE TEST CONTROL RESULTS USING THE SIGMA MATRIX METHOD IN THE LABORATORY OF HEART HOSPITAL DIAGRAM - Sabarina Elfrida Manik; Dianita Susanti; Aikut Yansen (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Quality control in triglyceride tests is carried out to improve the quality of test results and prevent irregularities, so that the accuracy and accuracy of test results can be guaranteed and trusted. Accuracy and accuracy are shown by the coefficient of variation and bias. Sigma matrix is a method to measure the performance of a process by analyzing the root of the problem and showing the number of error factors that occur. This study aims to analyze the results of triglyceride examination control using the sigma matrix method at the Diagram Heart Hospital Laboratory. The research methodology in this study is quantitative descriptive with a cross sectional design using a sample of triglyceride quality control data for the period March to May 2023 with 2 levels of control, namely normal and pathogenic. Sigma matrix analysis involves coefficient of variation (CV), bias and Total Allowable Error (TEa). In this study, the lowest sigma value was in April 2023 level 1 of 4.95 in the good category and the highest sigma value was in March level 1 of 11.73 which was included in the worldclass category, so there was no need to do QGI. The triglyceride control value in this study did not show any deviation at the level of the sigma and QGI matrix, so that the precision and accuracy of the triglyceride test results can be guaranteed in quality.